2020
DOI: 10.1002/masy.202000145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Modified Clays on the Mechanical Behavior of PC/ABS Polymer Blend

Abstract: Bentonite clay is surface modified and incorporated into PC/ABS (70/30) polymer blend by melt mixing in concentrations of 1, 3 and 5 wt% of clay. The efficiency of the treatments is analyzed by Fourier transform infrared spectroscopy (FTIR), x‐ray fluorescence (XRF) and x‐ray diffraction (XRD). Differential scanning calorimetry (DSC) and scanning electron microscopy (SEM) are used to evaluate the blends miscibility and morphology, respectively, and the mechanical behavior is analyzed by tensile tests. The meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The introduced multiwalled carbon nanotubes were not functionalized or modified prior to mixing, and therefore the TGA curves for the PC and PC/0.5%CN samples showed only a slight difference. The decrease in the value of thermal stability is a reflection of the high thermal conductivity of nanotubes, which can form locally high temperatures in their larger CN clusters, which was not observed in the case of the PC polymer matrix [ 50 ]. Observing the CN-containing composite (PC/0.5%CN), it showed greater weight loss ( Table 5 ) due to the low overheating effect [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduced multiwalled carbon nanotubes were not functionalized or modified prior to mixing, and therefore the TGA curves for the PC and PC/0.5%CN samples showed only a slight difference. The decrease in the value of thermal stability is a reflection of the high thermal conductivity of nanotubes, which can form locally high temperatures in their larger CN clusters, which was not observed in the case of the PC polymer matrix [ 50 ]. Observing the CN-containing composite (PC/0.5%CN), it showed greater weight loss ( Table 5 ) due to the low overheating effect [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The obtained result is confirmed by data obtained by other scientists [ 49 , 52 , 53 ]. Maintaining the same Tg values for all tested systems during the first and second heating ( Table 6 ) indicates that neither the content nor the modification of the filler surface affects the mixability [ 50 ]. Analyzing the thermograms obtained for the composites, one can also observe the second endothermic peak at a temperature of about 122 °C, which corresponds to the melting point of the added additive.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that the content of fillers in PC/ABS blends can improve thermal stability, tensile strength and elongation at break. The improvement of mechanical properties after introducing small amounts of MMT and small amounts of bentonite into the PC/ABS matrix has also been described by other scientists [ 19 , 20 ]. Researchers interested in electrically conductive composites [ 21 ] investigated the effects of graphene, carbon nanotubes and soot on the PC/ABS matrix.…”
Section: Introductionmentioning
confidence: 59%